Fungal Diseases of Tomato in Kathmandu Valley - Jha, Sanjay Kumar; Lamichhane, Sita (Journal of Nepal Biotechnology Association, 2023)
The infected parts of the tomato plant were collected from Jitpurphedi of Kathmandu, Nepal. The isolated fungi from the infected parts were Septoria lycopersici, Cladosporium oxysporum responsible for leaf spot, Phytophthora infestans and Rhizoctonia solani responsible for leaf blight, Cladosporium cladosporioides responsible for fruit rot, Leveilulla taurica responsible for powdery mildew and Plasmopara viticola responsible for Downey mildew disease. In the survey period, the highest incidence was found at leaf blight (30.08%) and the lowest at stem rot (4.64%). In the case of severity, the maximum severity was found at Downey mildew (77%) and the minimum was recorded at fruit rot (5.25%).